Finds of Coins of the Pontic State of the Mithridates Eupator on the Territory of the Northern and North-Eastern Part of Ukraine - Orlyk, Vasyl (Journal of Danubian Studies and Research, 2023)
The findings of Pontic coins on the territory of the Northern and North-Eastern part of Ukraine are analysed. The purpose of the research is to study and systematize the findings of coins of the Mithridates Eupator Pontic state in the Northern and North-Eastern part of Ukraine. For the first time in historiography, a study of coin finds of the cities of Pontus and Paphlagonia during the time of Mithridates Eupator was carried out on the territory of the Northern and North-Eastern part of Ukraine.